Introduction and evaluation of the ACS BCon basic course in Zaragoza, Spain. Issue 1 (12th January 2019) - Yanez, Carlos; Güemes, Antonio; Navarro, Ana; Vazquez, Jacqueline; Moreno, Alberto
Abstract : Background: The American College of Surgeons Bleeding Control Basic (BCon) course aimed at teaching hemorrhage control techniques in the USA had not yet been taught in Spain. The purpose of this study is to assess its implementation among students and healthcare employees in the Lozano Blesa University Hospital of Zaragoza, a middle-sized Spanish city. Methods: The study was conducted in a University Hospital and at the University of Zaragoza, scheduling four free B-Con sessions from 2017 to 2018. Two groups were identified as forming the population: healthcare employees and medical students. An anonymous questionnaire was completed at the end of the course regarding content, applicability, usefulness, relevance, and satisfaction. Study variables were ranked from 0 to 10: poor (when graded from 0 to 3), fair (4 to 6) and good (7 to 10). Results were compared between the groups, expressed in percentages and χ 2 tested to analyze significant differences if any. Results: Among the 83 individuals who completed the course, 46 were medical students and 37 healthcare employees; 61% women and 39% men; aged 21 years to 52 years. Attendees evaluated satisfaction with the highest grade (84%), followed by usefulness (73%), applicability (70%), and relevance (66%). There was no variable graded as poor. The comparison of perceptions between groups did not reveal statistical differences based on a 0.05 significance level. Conclusion: We concluded that the B-Con course was valued as good for relevance, usefulness, applicability, and satisfaction by the majority of the studied population. Level of evidence: Level III.